The Integration of Multiculturalism Values in School Management at Mts Favorit Darut Taqwa - Muhammad Yusuf; Maskuri (CV. Creative Tugu Pena, 2025)
This study examines the integration of multicultural values in school management at MTs Favorite Darut Taqwa. It focuses on how inclusive institutional policies, diversity-oriented learning programs, and the management of social interactions contribute to fostering tolerance and appreciation for differences within the madrasah environment. Employing a descriptive qualitative method, data were collected through observations, in-depth interviews, and document analysis. The findings reveal that MTs Favorit Darut Taqwa has successfully implemented non-discriminatory admission policies, incorporated multicultural values into the curriculum, and organized extracurricular activities that promote interaction among students from diverse backgrounds. Furthermore, the use of project-based learning and discussion methods has proven effective in enhancing students' awareness of cultural and social diversity. This study contributes to the discourse on multicultural education by providing insights into how school policies can foster a harmonious and inclusive learning environment. The findings offer valuable implications for madrasahs and other Islamic educational institutions in formulating policies that support multicultural education, with the aim of cultivating a tolerant generation with a strong national identity.